DDX3X and specific initiation factors modulate FMR1 repeat‐associated non‐AUG‐initiated translation. (25th July 2019) - Linsalata, Alexander E; He, Fang; Malik, Ahmed M; Glineburg, Mary Rebecca; Green, Katelyn M; Natla, Sam; Flores, Brittany N; Krans, Amy; Archbold, Hilary C; Fedak, Stephen J; Barmada, Sami J; Todd, Peter K
Abstract: A CGG trinucleotide repeat expansion in the 5′ UTR of FMR1 causes the neurodegenerative disorder Fragile X‐associated tremor/ataxia syndrome (FXTAS). This repeat supports a non‐canonical mode of protein synthesis known as repeat‐associated, non‐AUG (RAN) translation. The mechanism underlying RAN translation at CGG repeats remains unclear. To identify modifiers of RAN translation and potential therapeutic targets, we performed a candidate‐based screen of eukaryotic initiation factors and RNA helicases in cell‐based assays and a Drosophila melanogaster model of FXTAS. We identified multiple modifiers of toxicity and RAN translation from an expanded CGG repeat in the context of the FMR1 5′UTR. These include the DEAD‐box RNA helicase belle / DDX3X, the helicase accessory factors EIF4B/4H, and the start codon selectivity factors EIF1 and EIF5 . Disrupting belle / DDX3X selectively inhibited FMR1 RAN translation in Drosophila in vivo and cultured human cells, and mitigated repeat‐induced toxicity in Drosophila and primary rodent neurons. These findings implicate RNA secondary structure and start codon fidelity as critical elements mediating FMR1 RAN translation and identify potential targets for treating repeat‐associated neurodegeneration. Synopsis: Fragile X‐associated tremor/ataxia syndrome is caused by CGG repeat‐associated non‐AUG (RAN) translation that initiates within the 5′UTR of FMR1 . A candidate‐based screen identified several initiation factors—DDX3X/Belle, eIF4B, eIF4H, eIF1, and eIF5—critical for FMR1 RAN translation. Knockdown of the RNA helicase DDX3X selectively suppresses FMR1 RAN translation in Drosophila melanogaster, cultured HeLa cells, and in vitro translation assays. DDX3X knockdown reduces CGG repeat‐associated toxicity in Drosophila and mammalian neurons. Eukaryotic initiation factors that modulate RNA‐RNA secondary structure ( DDX3X, EIF4B, EIF4H ) or start codon fidelity ( EIF1, EIF5 ) impact FMR1 RAN translation. Abstract : FXTAS is caused by CGG repeat‐associated non‐AUG (RAN) translation that initiates within the 5′UTR of FMR1 . A candidate‐based screen identified several initiation factors—DDX3X/Belle, eIF4B, eIF4H, eIF1, and eIF5—critical for FMR1 RAN translation.